A standard's integrity can it be safeguarded?. - Egyedi, Tineke M. (IEEE Communications magazine)
When a compatibility standard is adapted, extended, or selectively implemented, its purpose is likely to be undermined. Its value declines sharply because interoperability between the standard-compliant implementations becomes uncertain. The integrity of the standard is at stake. This article discusses the strategies intended to safeguard the standards' integrity. The examples are set in the context of Java development, a de facto standard. The paper also discussed the manner and the degree of protecting the standard's integrity.